The impact of early childhood exposure to screens from language delay to EPEE syndrome - Touati, Meriem (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
For the past few years, children have consulted in pediatrics and child psychiatry, with serious clinical symptoms which can resemble autism spectrum disorders, coexisting with massive and very early exposure (before the age of 3) to screens. This has led specialists to speak of what is called "early and excessive exposure syndrome to the screens", being the heaviest consequence of early viewing of television, compared to the delay in language, which is also constituted a fairly frequent effect, the thing that we will tackle through a clinical case.